Bull bars and road trauma - Attewell, Robyn G. (CR, 2000)
This report investigates the positive and negative aspects of bull bars with regard to road trauma in Australia through assessment of the current literature and analysis of fatal road crash data. Quantification of risk is limited by a number of factors, including restricting the analysis to fatal crashes, incompleteness of data on the bull bar status of vehicles involved in crashes, lack of data on animal strikes and the difficulty of isolating effects of bull bars from other factors associated with injury outcomes, such as vehicle size and speed. Current improvements in bull bar design may offset the risks for pedestrians and other vulnerable road users predicted by experimental studies and the possible risks indicated in an analysis of side impact crashes.